Perspectives in business informatics research : 15th International Conference, BIR 2016, Prague, Czech Republic, September 15-16, 2016, Proceedings /: 15th International Conference, BIR 2016, Prague, Czech Republic, September 15-16, 2016, Proceedings. (2016) - Unknown
No abstract available